A Regional Dynamic General-Equilibrium Model of Alternative Climate-Change Strategies - Nordhaus, William D.; Yang, Zili (American Economic Review, 1996)
Most analyses treat global warming as a single-agent problem. The present study presents the Regional Integrated model of Climate and the Economy (RICE) model. By disaggregating into countries, the model analyzes different national strategies in climate-change policy: pure market solutions, efficient cooperative outcomes, and noncooperative equilibria. This study finds that cooperative policies show much higher levels of emissions reductions than do noncooperative strategies; that there are substantial differences in the levels of controls in both the cooperative and the noncooperative policies among different countries; and that high-income countries may be the major losers from cooperation.